Desk set [videorecording (DVD)] - Lang, Walter, 1898-1972; Tracy, Spencer, 1900-1967; Hepburn, Katharine, 1907-2003; Young, Gig, 1913-1978; Blondell, Joan; Marchant, William, 1923- (Studio classic, 2004)
A computer expert is brought in to raise the efficiency of a library in a television network research department.